Differential effects of instructed and objective feedback reliability on feedback‐related brain activity. (27th May 2019) - Di Gregorio, Francesco; Ernst, Benjamin; Steinhauser, Marco
Abstract: Feedback reliability refers to the probability that the same decision leads to the same positive or negative feedback in the future. Previous research has shown that unreliable feedback is associated with attenuated feedback‐related brain activity in ERPs, represented by a reduced fronto‐central valence effect (feedback‐related negativity or reward positivity) and a reduced feedback‐related P3. Here, we asked whether these effects reflect top‐down mechanisms or whether they can be explained by implicit feedback‐outcome contingency learning. In two experiments, participants performed a trial‐and‐error learning task while subjective or objective feedback reliability was varied across blocks. In Experiment 1, we manipulated instructed feedback reliability while holding objective feedback reliability constant. Low instructed feedback reliability led to an attenuation of the fronto‐central valence effect and the P3. In Experiment 2, we manipulated objective feedback reliability while holding instructed feedback reliability constant. Here, no modulation of feedback‐related brain activity was observed. These results suggest that effects of feedback reliability are driven by top‐down mechanisms based on explicit knowledge. Specifically, effects on the fronto‐central valence effect could indicate a devaluation of unreliable feedback or a bias on the generation or utilization of reward prediction errors. Abstract : Using unreliable feedback for learning is detrimental for subsequent decision making and thus should be avoided. The present study aimed to forward our understanding of how learning from feedback is modulated to reduce the utilization of unreliable feedback. We found that feedback‐related brain activity in a learning task was attenuated only when participants were instructed that feedback was unreliable but not when it was objectively unreliable. Based on these results, we identify top‐down devaluation or suppression of subjectively unreliable feedback as the central mechanism by which learning from potentially invalid feedback is avoided.